Peppermint extract improves egg production and quality, increases antioxidant capacity, and alters cecal microbiota in late-phase laying hens - Bai, Miaomiao; Liu, Hongnan; Zhang, Yihui; Wang, Shanshan; Shao, Yirui; Xiong, Xia; Hu, Xin; Yu, Rongyao; Lan, Wei; Cui, Yadong; Kong, Xiangfeng (Frontiers in Microbiology, 2023)
Introduction: Peppermint contains substantial bioactive ingredients belonging to phytoestrogen, and its effects on the production of late laying hens deserve more attention. This study evaluated the effects of dietary peppermint extract (PE) supplementation on egg production and quality, yolk fatty acid composition, antioxidant capacity, and caecal microbiota in late-phase laying hens.Method: PE powder was identified by UPLC-MS/MS analysis. Two hundred and sixteen laying hens (60-wk-old) were randomly assigned into four treatments, each for 28 days: (i) basal diet (control group, CON); (ii) basal diet + 0.1% PE; (iii) basal diet + 0.2% PE; (iiii) basal diet + 0.4% PE. Eggs, serum and cecal contents samples were collected for analysis.Results: Dietary PE supplementation increased the laying rate, serum triglyceride, immunoglobulin G, and total antioxidant capacity, while 0.2% and 0.4% PE supplementation increased eggshell thickness, serum total protein level, and superoxide dismutase activity of laying hens compared with the CON group (P < 0.05). Dietary PE addition in diets increased the C14:0, C18:3n3, C18:3n6, C23:0, C24:0, and C24:1n9 contents in the yolk. In addition, the egg yolk saturated fatty acid content was higher (P < 0.05) in the 0.2% and 0.4% PE groups compared with the CON and 0.1% PE groups.The microbiota analysis revealed that the caecal phylum Proteobacteria was decreased (P < 0.05) in the PE-supplemented groups. 0.4% PE supplementation increased the caecal richness of Grampositive bacteria and decreased the richness of Gram-negative and potentially pathogenic bacteria compared with the 0.1% PE group (P < 0.05). Microbial functions prediction analysis showed that the caecal microbiota of the PE group was mainly enriched by fatty acid degradation, fatty acid metabolism, amino sugar and nucleotide sugar metabolism, and other pathways. Regression analysis suggested that 0.28 -0.36% PE supplementation was the optimal level for improving egg production and quality, antioxidant capacity, and yolk fatty acid in late-phase laying hens.Discussion: Dietary PE supplementation improved egg production and quality (including yolk fatty acid composition) by increasing serum IgG and antioxidant capacity and modulating the intestinal microbiota in late-phase laying hens.